SYNTHESIS, CHARACTERIZATION AND ANTIBACTERIAL ACTIVITY OF A NEW DERIVATIVE OF LEVOFLOXACIN - Aura Rusu; Silvia Imre; Anca Delia Mare; Ioana-Andreea Lungu; Giorgiana-Andreea Pascu; Valentina Uivarosi (Journal of the Chilean Chemical Society, 2020)
A new levofloxacin derivative using silver triflate with antibacterial activity was synthesized and characterized. The new compound has been physicochemically characterized through elemental analysis, spectroscopic and thermal methods. All correlated experimental data suggested that the levofloxacin triflate was obtained. The antibacterial activity of the new compound was tested against six Gram-positive and Gram-negative bacteria. In vitro, the new compound had similar activity to levofloxacin against Staphylococcus aureus, Escherichia coli and Klebsiella pneumoniae and very closed to the minimum inhibitory concentration values of levofloxacin against Staphylococcus aureus MRSA, Enterococcus faecalis, and Pseudomonas aeruginosa.